Penguatan Dasar Kepemimpinan dan Komitmen OSIS Melalui Pengembangan Konten Edukasi Berbasis Proyek di SMK Darusalam 2 Pamulang - Mishellia Aprilian; Ifa Faizah; Debora Suranti; Lufthansa Chabsoh; Siti Wartini; Rusmiyati Rusmiyati; Herdi Wisman Jaya; Ersam Mahendrawan; Akhirudin Akhirudin (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2026)
This community service (PKM) program addresses the limited digital literacy, lack of formal leadership training, and social media publication challenges faced by the Student Council (OSIS) at SMK Darussalam 2 Pamulang. The initiative aimed to strengthen foundational leadership, organizational commitment, and digital creativity among student leaders. Utilizing a Project-Based Learning (PjBL) framework, the method combined observational assessments, interactive training simulations, and hands-on collaborative workshops. Thirty OSIS members participated in groups to identify urgent school challenges—such as bullying and indiscipline—and conceptualize solutions by producing creative educational posters. The findings revealed significant behavioral progress, marked by increased confidence in public speaking, enhanced teamwork, and an improved capacity to translate abstract concepts into persuasive digital media. The implications of this program highlight the viability of project-based community frameworks to bridge the gap between academic theory and vocational practice, transforming student councils into proactive digital agents of change within modern school ecosystems.